Impact of a rapid high‐sensitivity troponin pathway on patient flow in an urban emergency department. Issue 3 (5th May 2022) - Suh, Edward Hyun; Tichter, Aleksandr M.; Ranard, Lauren S.; Amaranto, Andrew; Chang, Betty C.; Huynh, Phong Anh; Kratz, Alexander; Lee, Rebekah Jihae; Rabbani, LeRoy E.; Sacco, Dana; Einstein, Andrew J.
Abstract: Study Objective: To evaluate whether the introduction of a 1‐hour high‐sensitivity cardiac troponin‐T (hs‐TnT) pathway for patients who present to the emergency department (ED) with suspected acute coronary syndrome (ACS) improves ED patient flow without changing the rate of "missed" major adverse cardiac events (MACE), compared to use of conventional cardiac troponin with an associated 3‐hour pathway. Methods: This was a prospective, uncontrolled observational study conducted before and after implementation of a 1‐hour hs‐TnT pathway at a high‐volume urban ED. Patients undergoing evaluation for ACS in the ED were enrolled during their initial visit and clinical outcomes were assessed at 30 and 90 days. Throughput markers were extracted from the electronic medical record and compared. The primary outcome was provider‐to‐disposition decision time. Results: A total of 1892 patients were enrolled, 1071 patients while using conventional troponin and 821 after introduction of hs‐TnT. With the new assay and pathway, median interval between troponin tests decreased from 4.7 hours (interquartile range [IQR] 3.9–5.7 hours) to 2.3 hours (IQR 1.5–3.4 hours) ( P < 0.001). However, there was no difference in median provider‐to‐disposition decision time, which measured 4.7 hours (IQR 2.9–7.2) and 4.8 hours (IQR 3.1–7.1) ( P = 0.428) respectively. Total 30‐day MACE rate in discharged patients was low in both groups, occurring in only 4/472 (0.85%) encounters in the first cohort and 4/381 (1.0%) encounters in the second. Conclusion: Introduction of a 1‐hour hs‐TnT ACS evaluation pathway reduced the troponin collection interval but did not reduce provider to disposition time. There was no difference in rate of 30‐day MACE in patients discharged from the ED.